2008
DOI: 10.4028/www.scientific.net/kem.396-398.277
|View full text |Cite
|
Sign up to set email alerts
|

Rietveld Refinement of Sintered Magnesium Substituted Calcium Apatite

Abstract: The incorporation of magnesium in the synthetic apatite has been associated with biomineralization process and osteoporosis therapy in human and animals. Magnesium easily replaces calcium in the apatite lattice and influences or controls the hydroxyapatite crystallization processes. In this work, Mg-substituted calcium deficient apatite, with Mg/Ca ratio = 0.1, 0.15 and 0.2 were synthesized by precipitation method. Then, sintered at 1000 oC and compared with a commercial product labeled as tricalcium phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
0
6
0
1
Order By: Relevance
“…Syntheses in bulk were realized by a precipitation method [46,71,172,173,[175][176][177][178][179][180][181][182][183][184][185][186], by sol-gel [187][188][189], in the presence of low molecular PAA [120], by the mechanochemical-hydrothermal route [174], by surfactantassisted microwave synthesis [190], by wet mixing [191] or by melting and extrusion [192].…”
Section: ϰ͘ϭ͘ϰ͘ ^ŝůŝđăƚğɛmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntheses in bulk were realized by a precipitation method [46,71,172,173,[175][176][177][178][179][180][181][182][183][184][185][186], by sol-gel [187][188][189], in the presence of low molecular PAA [120], by the mechanochemical-hydrothermal route [174], by surfactantassisted microwave synthesis [190], by wet mixing [191] or by melting and extrusion [192].…”
Section: ϰ͘ϭ͘ϰ͘ ^ŝůŝđăƚğɛmentioning
confidence: 99%
“…different methods for preparing HA-like materials would probably result in different levels of hydration and possibly other defects in the materials.Changes in lattice parameters due to substitution have a direct impact on the properties of Mg-HA, compared to their non-substituted analogues[47,172,174,178]: the changes notably increase their solubility and biodegradability in physiological fluids, and favour their thermal conversion into Mg-substituted ß-tricalcium phosphate (ß-Ca 3-x Mg x (PO 4 ) 2 )[185,186].Cacciotti et al[179] studied the effect of Mg substitution on sinterability, and they proved that Mg incorporation induced increased residual porosity. The influence of Mg concentration (up to 1.8 wt.%) on the mechanical properties of Mg-HA was the topic of a detailed study by…”
mentioning
confidence: 99%
“…The synthesized doped material becomes completely amorphous in nature when the Mg content reaches above 35 atom% [172]. On the other hand, Mg-substitution favors thermal conversion of HA into β-TCP [176]. Zyman et al [177] explored the mechanical properties of Mg-doped HA, and found a decline in its compressive strength and microhardness, together with an increment in fracture toughness.…”
Section: Divalent and Trivalent Cationsmentioning
confidence: 99%
“…Although several articles have already been published on the physicochemical properties of fluorapatites, carbonate-containing apatites and apatites with substituted and/or adsorbed various cations [1][2][3][4], only a few works were devoted to careful investigation of Mg 2+ -doped hydroxyapatite (Mg-HA) [5,8,[12][13][14][15][16][17][18] and Mg 2þ =CO 2À 3 co-substituted hydroxyapatite (Mg-CHA) [10,[19][20][21][22][23][24][25][26]. They reported various methods of the Mg-CHA syntheses, leading to various CO 2À 3 and Mg 2+ concentrations and different distributions of those ions between the crystal surface and the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%